Earnings and occupational attainment among immigrants - Chiswick, B.; Miller, Paul (Wiley-Blackwell Publishing Inc, 2009)
This paper examines the determinants of occupational attainment and the impact of occupation on earning among foreign-born men using the U.S. 2000 Census. Years of schooling and proficiency in English are the key factors determining access to high-paying occupations among immigrants. Foreign labor market experience, however, has a negative impact on current occupational status, especially among those in high-status jobs, due to the limited international transferability of skills acquired on the job.